2021
DOI: 10.1111/mcn.13220
|View full text |Cite
|
Sign up to set email alerts
|

Complementary feeding practices and associated factors of dietary diversity among uncomplicated severe acute malnourished children aged 6–23 months in Burkina Faso

Abstract: Nutritional treatment of children with uncomplicated severe acute malnutrition (SAM) is based on ready-to-use therapeutic foods (RUTF). With treatment provided at community level, children could have access to other foods, and a reduction in the dose of RUTF could further increase dietary diversity during treatment. We assessed the dietary diversity score (DDS), the minimum dietary diversity (MDD), the minimum meal frequency (MMF) and the minimum acceptable diet (MAD) of 459 infants and young children aged 6-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
3
5
0
Order By: Relevance
“…The predominance of these foods in diets is similar to the results of the SMART survey which found that these three food groups (cereals group, legumin's group and fruits group) were the most consumed in Burkina Faso in 2020 [29]. Other authors have also reported high consumption of cereals group, legumins group, vegetables and fruits group by children in Nigeria and Burkina Faso [28,30]. Meat products group (64.08%) and fruits and legumes rich in vitamin A group (53.56%) were also fairly consumed compared to the results of the SMART survey which reported the consumption of these food groups respectively at 47.2 % and 28.2% in the Central Region of Burkina Faso.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The predominance of these foods in diets is similar to the results of the SMART survey which found that these three food groups (cereals group, legumin's group and fruits group) were the most consumed in Burkina Faso in 2020 [29]. Other authors have also reported high consumption of cereals group, legumins group, vegetables and fruits group by children in Nigeria and Burkina Faso [28,30]. Meat products group (64.08%) and fruits and legumes rich in vitamin A group (53.56%) were also fairly consumed compared to the results of the SMART survey which reported the consumption of these food groups respectively at 47.2 % and 28.2% in the Central Region of Burkina Faso.…”
Section: Discussionsupporting
confidence: 78%
“…Regarding food consumption, cereals were the most consumed with a rate of 95.31%. Other authors had found similar rates with consumption of 94.4% in Zimbabwe [27] and 96% in Burkina Faso [28]. The other groups such as legumins, nuts and seeds group (83.01%) and other fruits and vegetables group (77.67%) were also mostly consumed.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This study is based on data collected prospectively as part of a randomized controlled trial (called MANGO), which compared the efficacy of a reduced RUTF dose to a standard RUTF dose in the management of SAM without medical complications in children 6–59 months of age in a non-inferiority design. The results from the randomized controlled trial have been published elsewhere [ 16 22 ]. The study recruited a total of 801 children which provides a good sample size for analysing predictors compared to previous studies looking at time to recovery with samples sizes starting from 200 and most around 400 children treated [ 23 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…This study is based on data collected prospectively as part of a randomized controlled trial (called MANGO), which compared the efficacy of a reduced RUTF dose to a standard RUTF dose in the management of SAM without medical complications in children 6-59 months of age in a non-inferiority design. The results from the randomized controlled trial have been published elsewhere [16][17][18][19][20][21][22]. The study recruited a total of 801 children which provides a good sample size for analysing predictors compared to previous studies looking at time to recovery with samples sizes starting from 200 and most around 400 children treated [23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Study Design and Settingmentioning
confidence: 99%